Presynaptic protein distribution and odour mapping in glomeruli of the olfactory bulb of Xenopus laevis tadpoles - Manzini, Ivan; Heermann, Stephan; Czesnik, Dirk; Brase, Christoph (European journal of neuroscience, 2007)
The sensory input layer in the olfactory bulb (OB) is typically organized into spheroidal aggregates of dense neuropil called glomeruli. This characteristic compartmentalization of the synaptic neuropil is a typical feature of primary olfactory centres in vertebrates and most advanced invertebrates. In the present work we mapped the location of presynaptic sites in glomeruli across the OB using antibodies to presynaptic vesicle proteins and presynaptic membrane proteins in combination with confocal microscopy. In addition the responses of glomeruli upon mucosal application of amino acid-odorants and forskolin were monitored using functional calcium imaging. We first describe the spatial distribution of glomeruli across the main olfactory bulb (MOB) in premetamorphic Xenopus laevis. Second, we show that the heterogeneous organization of glomeruli along the dorsoventral and mediolateral axes of the MOB is associated with a differential distribution of synaptic vesicle proteins. While antibodies to synaptophysin, syntaxin and SNAP-25 uniformly labelled glomeruli in the whole MOB, intense synaptotagmin staining was present only in glomeruli in the lateral, and to a lesser extent in the intermediate, part of the OB. Interestingly, amino acid-responsive glomeruli were always located in the lateral part of the OB, and glomeruli activated by mucosal forskolin application were exclusively located in the medial part of the OB. This correlation between odour mapping and presynaptic protein distribution is an additional hint on the existence of different subsystems within the main olfactory system in larval Xenopus laevis.
Gesehen am 22.06.2017